Enhancing the fracture properties of carbon fiber-calcium silicate hydrate interface through graphene oxide - Benzhi Min; Guoliang Chen; Yongyang Sun; Ke Li; Xi Chen; Zhenqing Wang (Materials & Design, 2024)
As a quasi-brittle material, concrete's toughness and durability are significantly affected by cracking. Extensive research has been focused on fiber reinforcing, a popular way to enhance concrete's mechanical properties. The bonding performance of the fiber–matrix interface plays a critical role in determining overall compatibility and microcrack formation. In this study, A series of all-atom models of the interface between carbon fibers (CF) and calcium silicate hydrates (C-S-H) were established and molecular dynamics simulations was used to investigate fiber pullout and uniaxial tensile response in the matrix. By incorporating graphene oxide (GO) sheets within the interface, the damage strength and critical energy release rate of the C-S-H and carbon fibers interface were significantly improved, with increases of 22.64% to 63.81% and 37.18% to 43.90%, respectively. Furthermore, the role of hydrogen bonding and interatomic interactions in resisting interfacial damage is clarified with delving into the intermolecular interactions inside the interface. Our study offers atomic-level insights into how nano-additives can enhance the mechanical performance of fiber-reinforced concrete (FRC), providing new ideas for the “bottom-up” design of high-performance concrete.